Energising your power utility - Poornalingam, R. (Faridabad, 2004)
The book is of immense utility particular ly in the present context when threats to our internal security make it incumbent on a citizen to bestir himself to play a meaning ful and effective role in the prevention of crime and violence.
Keywords: Electric power